The Implementation of Decentralization Reform Policy in Tanzania: The Case of Singida Municipality - Sulle, Dr. Andrew (International Journal of Scientific Research and Management (IJSRM), 2020)
The aim of this paper was to understand the implementation of decentralization policy in Tanzania. Just like many other countries in Africa and elsewhere, Tanzania has also adopted decentralization policy for various reasons. The main objectives of the paper was to assess and determine  the extent to which decentralization policy has been fully implemented in Tanzania and identify factors that inhibit effective implementation of the decentralization policy. The study used a case study design and Singida municipality was taken as focal point. Using both random and purposive sampling techniques, respondents were picked among councilors, top management and ordinary civil servants in Singida municipality.The main findings of this study are that decentralization reform has not been effectively implemented in Sindiga municipality. The municipality did not have autonomy and powers in many areas that e decentralization was supposed to empower them. Political will, institutional framework, resource constrains are among factors that inhibit effective implementation of decentralization policy in Tanzania. Our main conclusion is that effective implementation of decentralization would demand a strong institutional framework and political will, all of which are the missing ingredients in the case of Singida municipality.